The vertical mosaic revisited - Curtis, James E.; Helmes-Hayes, Richard C. (Richard Charles), 1951- (University of Toronto Press, 1998)
"When The Vertical Mosaic first appeared in 1965, it became an instant classic. Its key message was that Canada was not the classless democracy it fancied itself to be. In fact, Canada was a highly inegalitarian society comprising a 'vertical mosaic' of distinct classes and ethnic groups. This collection of papers by five of Canada's top sociologists subjects John Porter's landmark study to renewed scrutiny and traces the dramatic changes since Porter's time - both in Canadian society and in the agenda of Canadian sociology."--Jacket